Regional Expenditure, Human Development Index, and Economic Growth: Panel Data Evidence from Saireri - I Komang Giya Pramardika; Mesak Iek; Transna Putra Urip S (Global Academy of Business Studies, 2026)
Purpose: This study examines the effects of regional government expenditure on two key development outcomes — the Human Development Index (HDI) and economic growth — in the Saireri Customary Region of Papua Province, Indonesia. The four districts in this region (Biak Numfor, Kepulauan Yapen, Waropen, and Supiori) are characterized by a high dependence on central government transfers, significant inter-district HDI disparities, and heterogeneous economic growth trajectories. Despite these characteristics, an empirically rigorous analysis of regional expenditure effectiveness in this customary territory remains limited, particularly for the post-2015 period following Papua Special Autonomy Fund expansion. Research Methodology: A quantitative panel data approach was adopted, employing an unbalanced panel of 40 district-year observations across four districts from 2015 to 2024. Secondary data on HDI, GDP growth based on constant 2010 prices, and realized regional expenditure (transformed using the natural logarithm to normalize distribution) were obtained from BPS district-level statistical yearbooks (Kabupaten Dalam Angka) and Regional Government Financial Reports (LKPD). Two simple linear panel regression models were estimated: Model 1 with HDI as the dependent variable and Model 2 with economic growth as the dependent variable, both with (ln) regional expenditure as the predictor. Panel model selection followed the Chow (Pooled OLS vs. FEM) and Hausman (FEM vs. REM) tests. Heteroscedasticity was assessed using White’s test. The fixed effects model (FEM) was selected for Model 1 and the random effects model (REM) for Model 2. Results: Regional expenditure positively and statistically significantly affected the HDI (? = 14.724, t = 10.266, p = 0.000; Adjusted R² = 0.782). Cross-sectional fixed effects reveal that Biak Numfor has the strongest positive district-specific HDI trajectory (+4.21), while Supiori has the largest negative deviation (?3.42), reflecting structural disparities in public service delivery. Regional expenditure does not significantly influence economic growth in the Random Effect Model (? = ?0.359, t = ?0.154, p = 0.878; Adjusted R² = ?0.026), indicating that aggregate expenditure increases have not translated into measurable GRDP growth in the observation period. Conclusions: Regional expenditure in the Saireri Customary Region is significantly more effective in improving human development outcomes than in stimulating economic growth, suggesting structural weaknesses in the economic growth transmission mechanism of public expenditure in this remote Papua region. Limitations: The analysis uses aggregate regional expenditure without disaggregation by sector, the four-district, ten-year panel provides limited degrees of freedom, and causal inference is constrained by the cross-sectional dependence structure of the data. Contributions: This study provides the first systematic panel data analysis of regional expenditure effectiveness in the Saireri Customary Region, advancing the understanding of fiscal decentralization outcomes in remote Papua contexts and demonstrating the divergence between HDI and economic growth responses to government spending, a finding with direct implications for Papua Special Autonomy Fund allocation strategy.